On-line image-guided HDR brachytherapy (IGBT) for prostate cancer using ultrasound based real-time solution. (January 2019) - Yeo, A; George, K; Krishnan, P; Kron, T
Abstract: A new solution exists for prostate HDR brachytherapy, allowing seamless real-time procedure based on ultrasound imaging, compared a conventional approach with separate sessions for catheter insertion, CT imaging, planning and verification before treatment. This introduces a new paradigm into HDR brachytherapy procedure – no requirement for patient transfer while enabling real-time image guidance throughout the procedure including 'beam-on' time. In this work a seamless integration of real-time workflow has been designed, which demonstrates the efficacy of 'plan and treat' solution, in particular, with minimising geometric miss via a new on-line image guidance protocol.